Platelet Lysate Therapy Attenuates Hypoxia Induced Apoptosis in Human Uroepithelial SV-HUC-1 Cells through Regulating the Oxidative Stress and Mitochondrial-Mediated Intrinsic Apoptotic Pathway - Zong-Sheng Wu; Hou-Lun Luo; Yao-Chi Chuang; Wei-Chia Lee; Hung-Jen Wang; Michael B. Chancellor (Biomedicines, 2023)
(1) Background: Ischemia/hypoxia plays an important role in interstitial cystitis/bladder pain syndrome (IC/BPS). Platelet-rich plasma (PRP) has been shown to relieve symptoms of IC/BPS by regulating new inflammatory processes and promoting tissue repair. However, the mechanism of action of PRP on the IC/BPS bladder remains unclear. We hypothesize that PRP might protect the urothelium during ischemia/hypoxia by decreasing apoptosis. (2) Methods: SV-HUC-1 cells were cultured under hypoxia for 3 h and treated with or without 2% PLTGold® human platelet lysate (PL). Cell viability assays using trypan blue cell counts were examined. Molecules involved in the mitochondrial-mediated intrinsic apoptosis pathway, HIF1α, and PCNA were assessed by Western blot analysis. The detection of apoptotic cells and CM-H2DCFDA, an indicator of reactive oxygen species (ROS) in cells, was analyzed by flow cytometry. (3) Results: After 3 h of hypoxia, the viability of SV-HUC-1 cells and expression of PCNA were significantly decreased, and the expression of ROS, HIF1α, Bax, cytochrome c, caspase 3, and early apoptosis rate were significantly increased, all of which were attenuated by PL treatment. The addition of the antioxidant N-acetyl-L-cysteine (NAC) suppressed the levels of ROS induced by hypoxia, leading to inhibition of late apoptosis. (4) Conclusions: PL treatment could potentially protect the urothelium from apoptosis during ischemia/hypoxia by a mechanism that modulates the expression of HIF1α, the mitochondria-mediated intrinsic apoptotic pathway, and reduces ROS.